Recent Publications (Quarterly Journal of Economics, 1942)
Recent Publications The Quarterly Journal of Economics, Volume 56, Issue 3, May 1942, Pages 503–506, https://doi.org/10.1093/qje/56.3.503 Published: 01 May 1942